Mean ± SD of parameters extracted from calls of type E (Eistla), C (calf), F (Freya), and T (Thora). - Audra E. Ames (11349386); Susanna B. Blackwell (10013873); Outi M. Tervo (10013864); Mads Peter Heide-Jørgensen (7869812) (2021)
Mean ± SD of parameters extracted from calls of type E (Eistla), C (calf), F (Freya), and T (Thora).